Long Non-coding RNA DLEU1 Promotes Proliferation and Invasion by Interacting With miR-381 and Enhancing HOXA13 Expression in Cervical Cancer - Liu, Chang; Tian, Xing; Zhang, Jing; Jiang, Lifeng (Frontiers in Genetics, 2018)
Although growing evidence has demonstrated that the long noncoding RNA DLEU1 is involved in the progression of various cancers, its functional role and underlying mechanisms have not been explored in cervical cancer (CC). In this study, we found that DLEU1 was up-regulated in both CC tissues and CC cell lines, and overexpression of DLEU1 was significantly correlated with shorter patient survival. Knockdown of DLEU1 suppressed CC cell proliferation and invasion, whereas overexpression of DLEU1 promoted the proliferation and invasion of CC cells. Bioinformatics analysis was used to elucidate the potential correlation between DLEU1 and miR-381. Moreover, qRT-PCR analysis, luciferase reporter assay and RNA immunoprecipitation assay confirmed that DLEU1 inhibited the expression of miR-381, and revealed a direct interaction between DLEU1 and miR-381. In addition, we demonstrated that miR-381 directly targeted HOXA13 in CC cells. The restoration of HOXA13 expression reversed DLEU1 knockdown or miR-381 overexpression-mediated suppression of cell proliferation and invasion. These results suggested that DLEU1 can promote CC cell proliferation and invasion via the miR-381/HOXA13 axis.